Pembuatan Peta Portabel Usaha Keramba Budidaya Ikan Berbasis Android Smart Phone Di Sepanjang Sungai Martapura Kota Banjarmasin - Faris Ade Irawan; Effan Najwaini (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2021)
Smartphones that we have are equipped with various android-based applications that are distributed free of charge but are very useful and can be used optimally if we know how to use them, one such application is the Carrymap Observer. This application allows us to display maps offline on a smart phone but can integrate with GPS and can be manipulated by users directly. We make portable maps according to the theme we want which will be accessed on andoid smart phones that we have using Arc GIS devices so that they can be used anytime, anywhere as needed. Banjarmasin is also called the City of Thousand Rivers, a city that has many rivers, both large and small. Martapura River is one of the largest rivers and divides through the city of Banjarmasin. Banjarmasin City residents utilize the Martapura River as an economic and transportation center. on the banks of the River Martapura lined cages owned by residents. The floating net boxes are in groups. There are dozens, some are only a few. The farmers raise several types of fish. The majority of catfish and pomfret. The existence of these cages needs to be inventoryed to make it easier to monitor so that the good and bad impacts that are directly related to these business activities can be managed and monitored by related parties. From this research, a portable map based on Android smart phone is produced, it is offline and can be operated quickly via a smart phone anytime and anywhere. provide information about ownership, types of fish being cultivated and other information deemed important. Based on researchers' searches on Google Scholar, no similar studies were found, namely the theme of making portable maps of floating fish cages along the Martapura River in Banjarmasin. So this research needs to be done in order to add to the literature and references to support further research, because there are many benefits that we can get from the portable maps produced, the creation of a database of floating aquaculture and the application of science in the field of geospatial.